Unraveling the cGAS catalytic mechanism upon DNA activation through molecular dynamics simulations. Issue 15 (13th April 2021) - Soler, Jordi; Paiva, Pedro; Ramos, Maria J.; Fernandes, Pedro A.; Brut, Marie
Abstract : MD simulations are used to provide insights into cGAS activation upon DNA binding and to explore its role in the catalysis of cGAMP production. Two catalytic routes are proposed, suggesting that the ATP–GTP mechanism is favored over the GTP-ATP one. Abstract : Cyclic GMP-AMP Synthase (cGAS) is activated upon DNA binding and catalyzes the synthesis of 2′, 3′-cGAMP from GTP and ATP. This cyclic dinucleotide is a messenger that triggers the autoimmune system of eukaryotic cells. In this study, we propose a Molecular Dynamics (MD) investigation of cGAS activation. We notably provide insights into the motion of the activation loop, both from a mechanical point of view and considering its role in the catalysis of cGAMP production. We finally shed light on the reaction resulting in cGAMP synthesis. Two possible catalytic routes (referred to as GTP-ATP and ATP–GTP) are proposed based on the active site occupancy, paving the way toward further exploration of the reaction mechanism.